Peritoneal Dialysis Can Be an Option for Dominant Polycystic Kidney Disease: an Observational Study - Janeiro, Darío (Perit Dial Int, 2015)
♦ BACKGROUND: Autosomal dominant polycystic kidney disease (ADPKD) has been considered a relative contraindication for peritoneal dialysis (PD), although there are few specific studies available. ♦ METHODS: A multicenter historical prospective matched-cohort study was conducted to describe the outcome of ADPKD patients who have chosen PD. All ADPKD patients starting PD (n = 106) between January 2003 and December 2010 and a control group (2 consecutive patients without ADPKD) were studied. Mortality, PD-technique failure, peritonitis, abdominal wall leaks and cyst infections were compared. ♦ RESULTS: Patients with ADPKD had similar age but less comorbidity at PD inclusion: Charlson comorbidity index (CCI) 4.3 (standard deviation [SD] 1.6) vs 5.3 (SD 2.5) p < 0.001, diabetes mellitus 5.7% vs 29.2%, p < 0.001 and previous cardiovascular events 10.4% vs 27.8%, p < 0.001. No differences were observed in clinical events that required transient transfer to hemodialysis, nor in peritoneal leakage episodes or delivered dialysis dose. The cyst infection rate was low (0.09 episodes per patient-year) and cyst infections were not associated to peritonitis episodes. Overall technique survival was similar in both groups. Permanent transfer to hemodialysis because of surgery or peritoneal leakage was more frequent in ADPKD. More ADPKD patients were included in the transplant waiting list (69.8 vs 58%, p = 0.04) but mean time to transplantation was similar (2.08 [1.69 – 2.47] years). The mortality rate was lower (2.5 vs 7.6 deaths/100 patient-year, p = 0.02) and the median patient survival was longer in ADPKD patients (6.04 [5.39 – 6.69] vs 5.57 [4.95 – 6.18] years, p = 0.024). ♦ CONCLUSION: Peritoneal dialysis is a suitable renal replacement therapy option for ADPKD patients.